Application of Green Architecture Principles in Umbulan Pasuruan Natural Tourism Design - Krisnawangseh, Afni; Mutiara, Elok; Bahar, Mohammad Arsyad (Proceedings of the International Conference on Green Technology; Vol 10 (2019): Proceeding of International Conference on Green TechnologyDO - 10.18860/icgt.v10i0.1167, 2020)
Green architecture is an architecture that consumes natural resources, including energy, water, and material, and minimizes negative impacts on the environment. Green architecture is a step to realize sustainable human life. Green architecture has 3 main principles, namely: energy savings, utilization of renewable energy and the use of local materials. Of the three principles above, it will be applied to pennant natural tourism. Natural tourism is a form of recreation and tourism that utilizes the potential of natural resources, namely a source of water, both in natural conditions and after cultivation, allowing tourists to get physical and spiritual freshness, gain knowledge and experience, and grow inspiration and love for nature.